Connecting ambient toxicity testing with community-level responses of benthic macroinvertebrates in an impacted stream in East Tennessee, USA - Louise M. Stevenson; Paul G. Matson; Peyton C. Marcum; Nikki J. Jones; Scott C. Brooks; Trystan Bordeau; Allison M. Fortner; Natalie A. Griffiths; Christopher R. DeRolph; R. Trent Jett; Michael W. Jones; Peijia Ku; et al. (Journal of Environmental Management, 2026)

Differences in PFAS exposure between Pacific pinnipeds: The Galapagos (Zalophus wollebaeki) and California (Zalophus californianus) sea lions - Ashley E. Cave; Isabella G. Livingston; Taylor M. Gregory; Eleanor C. Hawkins; Shelly Vaden; Marjorie Riofrío-Lazo; Diane Deresienski; Gregory A. Lewbart; Anthony J. Orr; Emily Griffith; Christopher Fuller; Mark J. Strynar; et al. (Marine Pollution Bulletin, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Nitrogen cycling in a high-nutrient tidal river revealed through high-resolution sampling and nitrate isotope mixing models - Josh Guyat; Douglas R. Tait; James Z. Sippo; Benjamin T. Stewart; Angus Ferguson; James A. Padilla-Montalvo; Christopher Ralph; Jenny Rogers; Merran Griffith; Dirk V. Erler; Michael Ingram; Damien T. Maher (Geochimica et Cosmochimica Acta, 2026)

Assessing the Progress of Stock Rebuilding in the Northeast Atlantic Against Levels That Can Produce Maximum Sustainable Yield - Henning Winker; Massimiliano Cardinale; Rishi Sharma; Laurence T. Kell; Iago Mosqueira; Christopher Griffiths (Fish and Fisheries, 2026)
Rebuilding fish stocks to levels above which they produce Maximum Sustainable Yield (MSY) is a management aim for all European commercially exploited stocks. Progress is typically monitored against the fishing mortality that produces MSY in the long term ( F MSY ), however, the corresponding biomass target ( B MSY ) is rarely evaluated nor reported. Here, we analyse a unique database of 73 quantitative ICES stock assessments to provide estimates of B MSY across the Northeast Atlantic and apply a Bayesian state‐space model to estimate joint trajectories of F / F MSY and B / B MSY . Our results confirm that median fishing mortality has substantially decreased from its peak in 1999 to just below F MSY in 2020. Despite this, approximately half of the stocks remain fished above F MSY , with 36% exceeding 1.2 × F MSY . Biomass increased on average from below 0.5 B MSY in 2000 to 0.68 B MSY in 2020, but only 40% of stocks are currently above B MSY and only 35% have an age structure that is comparable with fishing at F MSY . Biomass relative to the ICES trigger point (MSY B trigger ) indicates that more than 70% of stocks are currently within safe biological limits. However, using MSY B trigger as a surrogate for B MSY results in an over‐optimistic classification of stock status, which conflicts with past levels of exploitation and may hinder stock rebuilding and the achievement of MSY objectives. Future projections from individual assessment forecasts predict further increases in B / B MSY under current F levels. However, to achieve B MSY by 2030, a ‘perfect’ implementation of the ICES Advice Rule would be required.

Factors affecting 87Sr/86Sr preservation in conodont apatite: An example from the Ordovician of Baltoscandia - Christopher T. Conwell; Matthew R. Saltzman; Anders Lindskog; Mats E. Eriksson; Elizabeth M. Griffith; Stephen A. Leslie; Cole T. Edwards; Olle Hints; Achim D. Herrmann (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

The Critical Role of Coefficients: Updating Allometric Normalisation Constants for Modern Ecology and Modelling - Penelope S. A. Blyth; Thomas F. Johnson; Thomas Malpas; Hana Mayall; Alina Smith; Alain Danet; Eva Delmas; Christopher A. Griffiths; Benno I. Simmons; John Jackson; Ulrich Brose; Andrew P. Beckerman (Ecology Letters, 2026)
Allometry, the scaling of traits or biological rates with body mass, is central to a wide range of ecological research including dynamic food web modelling. There has been extensive focus on exponents (3/4 scaling laws), but little on the coefficients (normalisation constants). Coefficients that have been used since 2006 are derived from limited data and dated methodologies. Here, we compiled a data set of over 1000 genera with body mass spanning 10 orders of magnitude. We updated metabolism and production coefficients, deriving new genus and metabolic group levels estimates with phylogenetic hierarchical modelling providing robust inference. Our coefficients were mostly lower than those previously estimated, with increased uncertainty estimates. We used the Bioenergetic Food Web Model to evaluate their impact, finding increased biomass and species persistence but no change in stability. Our coefficients pave the way for future simulations that take advantage of subsets of genus and metabolic group data.

Patterns and thresholds for soil pH across Europe in relation to soil health and degradation - Inma Lebron; Christopher J. Feeney; Sabine Reinsch; Nima Shokri; Mehdi H. Afshar; Steve Lofts; Rob Griffiths; David Fidler; Briony Jones; Panos Panagos; Kasia Sawicka; Aidan M. Keith; et al. (CATENA, 2025)

Overlooked seasonal groundwater nutrient fluxes rival anthropogenic point sources across a variable land‐use tidal river - James A. Padilla‐Montalvo; Douglas R. Tait; Michael J. Reading; Benjamin T. Stewart; Angus Ferguson; Iremar Fernandez‐Vazquez; James Z. Sippo; Shivanesh Rao; Mitch Call; Christopher Ralph; Josh Guyat; Jenny Rogers; et al. (Limnology and Oceanography, 2025)
Understanding groundwater–surface water connectivity in tidal freshwater zones is essential for managing ecosystems within the riverine–estuarine continuum. Groundwater discharge is a key source of dissolved nutrient loads that can lead to eutrophication, deoxygenation, and other ecosystem imbalances in coastal environments. However, groundwater is an often‐overlooked nutrient delivery pathway, with limited studies quantifying groundwater inputs into freshwater transitional zones. Here, we quantify groundwater discharge and its associated nutrient fluxes along a ≈ 75 km section of a tidal freshwater zone within the Hawkesbury–Nepean River (New South Wales, Australia), which is surrounded by multiple land uses. High‐resolution timeseries and spatial surveys were employed over three hydrologically distinct seasons using the naturally occurring radioisotope tracer, radon. Survey results revealed decreasing surface water radon activity and nutrients toward the downstream estuarine boundary. Estimated groundwater discharge rates were highest in the upstream reaches (6.0–12.5 cm d −1 ), regardless of seasonal hydrological dynamics, and decreased downstream, aligning with a reduction in irrigation‐dependent agricultural practices and a change in adjacent catchment morphology. During the dry period, groundwater accounted for up to ≈ 68% of upstream river inputs. Groundwater discharge was also a major source of dissolved inorganic nitrogen, contributing between 0.8 and 1.1 times the inputs from local wastewater treatment plants, and up to 15 times more phosphate than upstream river sources. These findings highlight the role of groundwater discharge as a nutrient driver for tidal freshwater zones, which could have significant implications for future management strategies in these environments.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Shrinking shrimp - Investigating the weight loss of northern shrimp Pandalus borealis following boiling - Christopher A. Griffiths; Emilia Björklund; Nuno Prista; Axel Hjelm; Katja Norén; Lisa Sörman; Ronja Risberg; Massimiliano Cardinale; Mikaela Bergenius Nord (Fisheries Research, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Frameworks and best practices for cumulative impact accounting in offshore energy development - Caitlin D. Kuempel; Jackson Stockbridge; Tess O’Neill; Laura L. Griffiths; Christopher L.J. Frid; Christopher J. Brown (Marine Policy, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Cover crop cultivars and species differ in root traits potentially impacting their selection for ecosystem services - Kong M. Wong; Marcus Griffiths; Amelia Moran; Andrea Johnston; Alexander E. Liu; Mitchell A. Sellers; Christopher N. Topp (Plant and Soil, 2024)
Background and aims Cover crops have the potential to aid in adapting agricultural systems to climate change impacts through their ecosystem services, such as preventing soil erosion, remediating soil structure, and storing carbon belowground. Though roots are integral to these processes, there is a lack of cover crop root trait data. This study aims to characterize rooting behavior of several commercially available cover crops and assess how differences in root system architecture potentially impact their selection for ecosystem services. Methods Twenty-two cover crop cultivars across the grass, legume, and brassica families were grown in O’Fallon, Missouri, USA. Canopy cover was monitored throughout the growing season. Shoot and root biomass samples were collected and analyzed. Results Cereal rye and winter triticale were the most winter hardy cultivars and provided the highest percent canopy cover. Cereal rye and winter triticale also generated the highest amount of shoot and root biomass among treatments but diverged in their root system architectures. Winter triticale forms coarser roots and exhibited deeper rooting, which may be better suited for carbon sequestration. Rapeseed and Siberian kale have favorable C:N ratios for nutrient recycling, but rapeseed may invest more into lateral root formation and have a higher potential to “catch” excess nutrients. Conclusion Selection of cover crops for ecosystem services should account for root system architecture and their suitability for these ecosystem services. Differences in root traits among cultivars within the same family highlight the potential to breed cover crop root system architecture to further enhance ecosystem service efficacy.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

A data‐driven approach to multiple‐stressor impact assessment for a marine protected area - Laura L. Griffiths; Joel Williams; Christina A. Buelow; Vivitskaia J. Tulloch; Mischa P. Turschwell; Max D. Campbell; David Harasti; Rod M. Connolly; Christopher J. Brown (Conservation Biology, 2024)
The coastal environment is not managed in a way that considers the impact of cumulative threats, despite being subject to threats from all realms (marine, land, and atmosphere). Relationships between threats and species are often nonlinear; thus, current (linear) approaches to estimating the impact of threats may be misleading. We developed a data‐driven approach to assessing cumulative impacts on ecosystems and applied it to explore nonlinear relationships between threats and a temperate reef fish community. We used data on water quality, commercial fishing, climate change, and indicators of recreational fishing and urbanization to build a cumulative threat map of the northern region in New South Wales, Australia. We used statistical models of fish abundance to quantify associations among threats and biophysical covariates and predicted where cumulative impacts are likely to have the greatest impact on fish. We also assessed the performance of no‐take zones (NTZs), to protect fish from cumulative threats across 2 marine protected area networks (marine parks). Fishing had a greater impact on fish than water quality threats (i.e., percent increase above the mean for invertivores was 337% when fishing was removed and was 11% above the mean when water quality was removed inside NTZs), and fishing outside NTZs affected fish abundances inside NTZs. Quantifying the spatial influence of multiple threats enables managers to understand the multitude of management actions required to address threats.

Remedial effectiveness of a pond biomanipulation: Habitat value and concentrations of polychlorinated biphenyls in fish - Rebecca A. Efroymson; Mark J. Peterson; R. Trent Jett; Natalie A. Griffiths; Evin T. Carter; Allison M. Fortner; Christopher R. DeRolph; Peijia Ku; Paul G. Matson; Rachel M. Pilla; Teresa J. Mathews (Journal of Hazardous Materials, 2024)

Including older fish in fisheries management: A new age‐based indicator and reference point for exploited fish stocks - Christopher A. Griffiths; Henning Winker; Valerio Bartolino; Håkan Wennhage; Alessandro Orio; Massimiliano Cardinale (Fish and Fisheries, 2024)
Larger and older fish contribute disproportionately to spawning and play an important role in the replenishment of exploited stocks. Fishing often removes specific size‐ and age‐classes, with direct impacts on stock productivity and population resilience. Despite this, fisheries advice is commonly based on estimates of spawning stock biomass (SSB) and fishing mortality (F) and makes little reference to the importance of size and/or age structure. Consequently, there is a need for indicators of size and/or age structure to better inform fisheries management and help assess global sustainability goals. Here, we introduce a new age‐based indicator ABI MSY that monitors age structure relative to the equilibrium age structure at F MSY . We apply this new indicator to 72 commercially important stocks in the Northeast Atlantic, covering 26 species, which collectively contributed 86% of all commercial catches in the region in 2019. We estimate that 62% (45 stocks) currently have proportionally fewer older fish relative to F MSY conditions, whereas 38% (27 stocks) have proportionally more older fish; we also note patterns with respect to geographic area and taxonomic family. Simulation testing demonstrated that ABI MSY is responsive to overfishing and generally tracks (with high sensitivity and specificity) a common measure of stock depletion, SSB relative to B MSY . Throughout, we show that ABI MSY provides information on the age structure of exploited stocks that is complementary to conventional reference points for SSB and F . Further, the framework used to estimate ABI MSY make it well placed for integration into current advisory frameworks on fisheries management.

Effects of a mediterranean diet on the gut microbiota and microbial metabolites: A systematic review of randomized controlled trials and observational studies - Rachel Kimble; Phebee Gouinguenet; Ammar Ashor; Christopher Stewart; Kevin Deighton; Jamie Matu; Alex Griffiths; Fiona C. Malcomson; Abraham Joel; David Houghton; Emma Stevenson; Anne Marie Minihane; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Improved closed test setup for biodegradation testing of slightly volatile substances in water-sediment systems (OECD 308) - Prasit Shrestha; Christopher B. Hughes; Louise Camenzuli; Delina Lyon; Boris Meisterjahn; Thomas Hennecke; Megan Griffiths; Dieter Hennecke (Chemosphere, 2023)

What causes energy and transport poverty in Ireland? Analysing demographic, economic, and social dynamics, and policy implications - Christopher Lowans; Aoife Foley; Dylan Furszyfer Del Rio; Brian Caulfield; Benjamin K. Sovacool; Steven Griffiths; David Rooney (Energy Policy, 2023)

Rebuilding A Collapsed Bivalve Population, Restoring Seagrass Meadows, and Eradicating Harmful Algal Blooms In A Temperate Lagoon Using Spawner Sanctuaries - Christopher J. Gobler; Michael H. Doall; Bradley J. Peterson; Craig S. Young; Flynn DeLaney; Ryan B. Wallace; Stephen J. Tomasetti; Timothy P. Curtin; Brooke K. Morrell; Elizabeth M. Lamoureux; Berry Ueoka; Andrew W. Griffith; et al. (Frontiers in Marine Science, 2022)
During the past century, bivalve populations across the globe have collapsed, resulting in negative ecosystem consequences due to their outsized impact on shallow estuaries. In response, there has been strong interest in the restoration of marine bivalve populations. Here, we present a decade-long restoration effort that sought to rebuild a collapsed (99.5% reduction in harvest) and recruitment-limited population of hard clams ( Mercenaria mercenaria ) in Shinnecock Bay, NY, USA, using spawner sanctuaries: no-harvest zones where adults were planted at high densities (~27 m- 2 ). Between 2012 to 2019, more than 3.2 million clams were planted in 64 discrete sanctuary plots (~1,850 m 2 each) located in zones with maximal larval retention and sediment and seawater characteristics that would maximize the conditioning and spawning of adults. Hydrodynamic models, quantification of hard clam larvae, and spatial recruitment patterns demonstrated larvae spawned within sanctuaries were transported to regions where clam densities significantly increased 18-fold over seven years (2015-2021; p <0.001) and harvests significantly increased more than 16-fold over nine years (2012-2021; p <0.0001). Increases in populations and harvests were caused by smaller clams recruited within the time frame of the creation of spawner sanctuaries. Higher clam densities caused biological filtration times of the bay to decrease from up to three months at the start of the project to as low as 10 days in 2021. Concurrently, concentrations of the harmful brown tide alga, Aureococcus anophagefferens , and chlorophyll a significantly decreased ( p <0.005) while water clarity and the extent of seagrass beds significantly increased ( p <0.05). Increases in clam landings and improvements in water quality were not observed in adjacent lagoonal estuaries where restoration did not occur. Given these outcomes and the global need for rebuilding marine life, the implementation of spawner sanctuaries using the criteria set forth herein may be a promising approach for restoring hard clam and other bivalve populations in estuaries elsewhere.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Representing plant diversity in land models: An evolutionary approach to make “Functional Types” more functional - Leander D. L. Anderegg; Daniel M. Griffith; Jeannine Cavender‐Bares; William J. Riley; Joseph A. Berry; Todd E. Dawson; Christopher J. Still (Global Change Biology, 2022)
Plants are critical mediators of terrestrial mass and energy fluxes, and their structural and functional traits have profound impacts on local and global climate, biogeochemistry, biodiversity, and hydrology. Yet, Earth System Models (ESMs), our most powerful tools for predicting the effects of humans on the coupled biosphere–atmosphere system, simplify the incredible diversity of land plants into a handful of coarse categories of “Plant Functional Types” (PFTs) that often fail to capture ecological dynamics such as biome distributions. The inclusion of more realistic functional diversity is a recognized goal for ESMs, yet there is currently no consistent, widely accepted way to add diversity to models, that is, to determine what new PFTs to add and with what data to constrain their parameters. We review approaches to representing plant diversity in ESMs and draw on recent ecological and evolutionary findings to present an evolution‐based functional type approach for further disaggregating functional diversity. Specifically, the prevalence of niche conservatism, or the tendency of closely related taxa to retain similar ecological and functional attributes through evolutionary time, reveals that evolutionary relatedness is a powerful framework for summarizing functional similarities and differences among plant types. We advocate that Plant Functional Types based on dominant evolutionary lineages (“Lineage Functional Types”) will provide an ecologically defensible, tractable, and scalable framework for representing plant diversity in next‐generation ESMs, with the potential to improve parameterization, process representation, and model benchmarking. We highlight how the importance of evolutionary history for plant function can unify the work of disparate fields to improve predictive modeling of the Earth system.

Understanding and managing the interactive impacts of growth in urban land use and climate change on freshwater biota: A case study using the platypus ( Ornithorhynchus anatinus ) - Rhys A. Coleman; Yung En Chee; Nick R. Bond; Andrew Weeks; Josh Griffiths; Melody Serena; Geoff A. Williams; Christopher J. Walsh (Global Change Biology, 2022)
Globally, urban expansion and climate change interact to threaten stream ecosystems and are accelerating the loss of aquatic biodiversity. Waterway managers urgently need tools to understand the potential combined impacts of urbanization and climate change and to identify effective mitigating management interventions for protecting freshwater biota. We address this challenge using the semi‐aquatic mammal the platypus ( Ornithorhynchus anatinus ) as a focal species. We developed high‐resolution environmental spatial data for stream networks and spatially explicit habitat suitability models (HSMs) to explore the impact of threats and to identify the combination of management actions most likely to maintain or improve habitat suitability over the next 50 years in greater Melbourne, Australia. We developed and evaluated platypus HSMs (males‐and‐females and females‐only) including validation using an independent environmental DNA data set. Platypus occurred more commonly in larger, cooler streams with greater catchment‐weighted discharge, following periods of greater stream flow. They were positively associated with near‐stream forest cover and negatively associated with annual air temperature and urban stormwater runoff. Extensive reductions in suitable platypus habitat are predicted to occur under urbanization and climate change scenarios, with the greatest threat expected from reduced streamflows. This emphasizes the importance of maintaining flow regimes as part of conserving platypus in the region; however, substantial additional benefit is predicted by concurrent riparian revegetation and urban stormwater management efforts (that also have the potential to contribute to the streamflow objectives). Provision of adequate streamflows in a future with increasing water demands and water security requirements will likely require creative integrated water management solutions. Our high‐resolution stream network and HSMs have allowed predictions of potential range‐shifts due to urban expansion and climate change impacts at management‐relevant scales and at the whole‐of‐landscape scale. This has enabled systematic strategic planning, priority action planning and target setting in strategic policy development.

Poor relationships between NEON Airborne Observation Platform data and field‐based vegetation traits at a mesic grassland - Stephanie Pau; Jesse B. Nippert; Ryan Slapikas; Daniel Griffith; Seton Bachle; Brent R. Helliker; Rory C. O’Connor; William J. Riley; Christopher J. Still; Marissa Zaricor (Ecology, 2022)
Understanding spatial and temporal variation in plant traits is needed to accurately predict how communities and ecosystems will respond to global change. The National Ecological Observatory Network’s (NEON’s) Airborne Observation Platform (AOP) provides hyperspectral images and associated data products at numerous field sites at 1 m spatial resolution, potentially allowing high‐resolution trait mapping. We tested the accuracy of readily available data products of NEON’s AOP, such as Leaf Area Index (LAI), Total Biomass, Ecosystem Structure (Canopy height model [CHM]), and Canopy Nitrogen, by comparing them to spatially extensive field measurements from a mesic tallgrass prairie. Correlations with AOP data products exhibited generally weak or no relationships with corresponding field measurements. The strongest relationships were between AOP LAI and ground‐measured LAI ( r = 0.32) and AOP Total Biomass and ground‐measured biomass ( r = 0.23). We also examined how well the full reflectance spectra (380–2,500 nm), as opposed to derived products, could predict vegetation traits using partial least‐squares regression (PLSR) models. Among all the eight traits examined, only Nitrogen had a validation of more than 0.25. For all vegetation traits, validation ranged from 0.08 to 0.29 and the range of the root mean square error of prediction (RMSEP) was 14–64%. Our results suggest that currently available AOP‐derived data products should not be used without extensive ground‐based validation. Relationships using the full reflectance spectra may be more promising, although careful consideration of field and AOP data mismatches in space and/or time, biases in field‐based measurements or AOP algorithms, and model uncertainty are needed. Finally, grassland sites may be especially challenging for airborne spectroscopy because of their high species diversity within a small area, mixed functional types of plant communities, and heterogeneous mosaics of disturbance and resource availability. Remote sensing observations are one of the most promising approaches to understanding ecological patterns across space and time. But the opportunity to engage a diverse community of NEON data users will depend on establishing rigorous links with in‐situ field measurements across a diversity of sites.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Urbanisation weakens selection on the timing of breeding and clutch size in blue tits but not in great tits - Claire J. Branston; Pablo Capilla-Lasheras; Christopher J. Pollock; Kate Griffiths; Stewart White; Davide M. Dominoni (Behavioral Ecology and Sociobiology, 2021)
Urbanisation is a globally occurring phenomenon and is predicted to continue increasing rapidly. Urban ecosystems present novel environments and challenges which species must acclimate or adapt to. These novel challenges alter existing or create new selection pressures on behaviours which provide an opportunity to investigate eco-evolutionary responses to contemporary environmental change. We used 7 years of breeding data from urban and forest populations of blue and great tits to understand whether selection for timing of breeding or clutch size differed between the two habitats and species. We found that urban great tits laid eggs earlier than their forest counterparts, but there was no evidence of a difference in selection for earlier breeding. Blue tits, however, did not differ in timing of egg laying between the two habitats, but selection for earlier laying was weaker in the urban environment. Both species laid smaller clutches in the urban site and had positive selection for larger clutch sizes which did not differ in strength for the great tits but did for blue tits, with weaker selection in the urban population. Our results suggest that food availability for nestlings may be constraining urban birds, and that the temporal cues females use to time breeding correctly, such as tree budburst and food availability, may be absent or reduced in urban areas due to lower caterpillar availability. These results have implications for our understanding of the adaptation of wild animals to city life. Significance statement Urbanisation is expanding rapidly and changing the environment many species live in. A key challenge is to understand how species adapt to the urban environment, why some species can adapt, why others cannot and what we can do to ensure that cities are ecologically sustainable and biodiversity rich. Here we show that the strength of natural selection for early breeding and larger clutch size is weaker in urban than non-urban blue tits, likely due to reduced and irregular availability of natural insect food in urban areas. This effect was not found in great tits. Thus, urbanisation can alter the selection pressures wild animals are exposed to, but this effect may differ between species, even when closely related. This has implications for our understanding of how species adapt to urban life.

Nitrogen and phosphorus cycling in an ombrotrophic peatland: a benchmark for assessing change - Verity G. Salmon; Deanne J. Brice; Scott Bridgham; Joanne Childs; Jake Graham; Natalie A. Griffiths; Kirsten Hofmockel; Colleen M. Iversen; Terri M. Jicha; Randy K. Kolka; Joel E. Kostka; Avni Malhotra; et al. (Plant and Soil, 2021)

Building a bridge between adaptive capacity and adaptive potential to understand responses to environmental change - Travis Seaborn; David Griffith; Andrew Kliskey; Christopher C. Caudill (Global Change Biology, 2021)
Adaptive capacity is a topic at the forefront of environmental change research with roots in both social, ecological, and evolutionary science. It is closely related to the evolutionary biology concept of adaptive potential. In this systematic literature review, we: (1) summarize the history of these topics and related fields; (2) assess relationship(s) between the concepts among disciplines and the use of the terms in climate change research, and evaluate methodologies, metrics, taxa biases, and the geographic scale of studies; and (3) provide a synthetic conceptual framework to clarify concepts. Bibliometric analyses revealed the terms have been used most frequently in conservation and evolutionary biology journals, respectively. There has been a greater growth in studies of adaptive potential than adaptive capacity since 2001, but a greater geographical extent of adaptive capacity studies. Few studies include both, and use is often superficial. Our synthesis considers adaptive potential as one process contributing to adaptive capacity of complex systems, notes “sociological” adaptive capacity definitions include actions aimed at desired outcome (i.e., policies) as a system driver whereas “biological” definitions exclude such drivers, and suggests models of adaptive capacity require integration of evolutionary and social–ecological system components.

The Utility of Satellites and Autonomous Remote Sensing Platforms for Monitoring Offshore Aquaculture Farms: A Case Study for Canopy Forming Kelps - Tom W. Bell; Nick J. Nidzieko; David A. Siegel; Robert J. Miller; Kyle C. Cavanaugh; Norman B. Nelson; Daniel C. Reed; Dmitry Fedorov; Christopher Moran; Jordan N. Snyder; Katherine C. Cavanaugh; Christie E. Yorke; et al. (Frontiers in Marine Science, 2020)
The emerging sector of offshore kelp aquaculture represents an opportunity to produce biofuel feedstock to help meet growing energy demand. Giant kelp represents an attractive aquaculture crop due to its rapid growth and production, however precision farming over large scales is required to make this crop economically viable. These demands necessitate high frequency monitoring to ensure outplant success, maximum production, and optimum quality of harvested biomass, while the long distance from shore and large necessary scales of production makes in person monitoring impractical. Remote sensing offers a practical monitoring solution and nascent imaging technologies could be leveraged to provide daily products of the kelp canopy and subsurface structures over unprecedented spatial scales. Here, we evaluate the efficacy of remote sensing from satellites and aerial and underwater autonomous vehicles as potential monitoring platforms for offshore kelp aquaculture farms. Decadal-scale analyses of the Southern California Bight showed that high offshore summertime cloud cover restricts the ability of satellite sensors to provide high frequency direct monitoring of these farms. By contrast, daily monitoring of offshore farms using sensors mounted to aerial and underwater drones seems promising. Small Unoccupied Aircraft Systems (sUAS) carrying lightweight optical sensors can provide estimates of canopy area, density, and tissue nitrogen content on the time and space scales necessary for observing changes in this highly dynamic species. Underwater color imagery can be rapidly classified using deep learning models to identify kelp outplants on a longline farm and high acoustic returns of kelp pneumatocysts from side scan sonar imagery signal an ability to monitor the subsurface development of kelp fronds. Current sensing technologies can be used to develop additional machine learning and spectral algorithms to monitor outplant health and canopy macromolecular content, however future developments in vehicle and infrastructure technologies are necessary to reduce costs and transcend operational limitations for continuous deployment in an offshore setting.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Tropical Coastal Wetlands Ameliorate Nitrogen Export During Floods - Maria Fernanda Adame; Melanie E. Roberts; David P. Hamilton; Christopher E. Ndehedehe; Vanessa Reis; Jing Lu; Matthew Griffiths; Graeme Curwen; Mike Ronan (Frontiers in Marine Science, 2019)

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Differential Mortality of North Atlantic Bivalve Molluscs During Harmful Algal Blooms Caused by the Dinoflagellate, Cochlodinium (a.k.a. Margalefidinium) polykrikoides - Andrew W. Griffith; Sandra E. Shumway; Christopher J. Gobler (Estuaries and Coasts, 2019)

Assessing earth system model predictions of C 4 grass cover in North America: From the glacial era to the end of this century - Christopher J. Still; Jennifer M. Cotton; Daniel M. Griffith (Global Ecology and Biogeography, 2019)
Aim C 4 grasses are distinct from C 3 grasses, because C 4 grasses respond in a different manner to light, temperature, CO 2 and nitrogen and often have higher resource‐use efficiencies. C 3 and C 4 grasses are typically represented in earth system models (ESMs) by different plant functional types (PFTs). The ability of ESMs to capture C 4 grass biogeography and ecology across differing time periods is important to assess, given the crucial role they play in ecosystems and their divergent responses to global change. Location North America. Time periods Last Glacial Maximum (LGM), historical modern period ( ca . 1850) and end of this century. Major taxa studied C 4 grasses. Methods Proxy data representing relative cover and productivity of C 4 grasses were collated, including carbon isotope ratios of soil carbon and animal grazer tissue, and vegetation plot data in undisturbed grasslands. We selected available model predictions of C 4 PFT percentage cover. Models were compared against one another and assessed against proxy data at key time points: the LGM, the historical modern period before widespread grassland conversion to agriculture, and the end of this century. Results We highlight large differences among model predictions of percentage C 4 grass cover across North America: all pairwise combinations have correlations 4 grass cover from proxy data, during either the LGM or the historical modern period. Models generally under‐predict percentage C 4 grass cover, particularly during the historical modern period. Main conclusions Earth system models do not accurately represent the biogeography of C 4 grasses across a range of time‐scales, and their outputs do not agree with one another. We suggest model improvements to represent this crucial functional type better, including more collection and greater integration of C 3 and C 4 grass trait data, explicit representations of tree–grass competition for water, and a greater focus on disturbance ecology.

Temperature, Acidification, and Food Supply Interact to Negatively Affect the Growth and Survival of the Forage Fish, Menidia beryllina (Inland Silverside), and Cyprinodon variegatus (Sheepshead Minnow) - Christopher J. Gobler; Lucas R. Merlo; Brooke K. Morrell; Andrew W. Griffith (Frontiers in Marine Science, 2018)

Endocytic Uptake, Transport and Macromolecular Interactions of Anionic PAMAM Dendrimers within Lung Tissue - Christopher J. Morris; Ghaith Aljayyoussi; Omar Mansour; Peter Griffiths; Mark Gumbleton (Pharmaceutical Research, 2017)

Multi‐century stasis in C 3 and C 4 grass distributions across the contiguous United States since the industrial revolution - Daniel M. Griffith; Jennifer M. Cotton; Rebecca L. Powell; Nathan D. Sheldon; Christopher J. Still (Journal of Biogeography, 2017)
Aims Understanding the functional response of ecosystems to past global change is crucial to predicting performance in future environments. One sensitive and functionally significant attribute of grassland ecosystems is the percentage of species that use the C 4 versus C 3 photosynthetic pathway. Grasses using C 3 and C 4 pathways are expected to have different responses to many aspects of anthropogenic environmental change that have followed the industrial revolution, including increases in temperature and atmospheric CO 2 , changes to land management and fire regimes, precipitation seasonality, and nitrogen deposition. In spite of dramatic environmental changes over the past 300 years, it is unknown if the C 4 grass percentage in grasslands has shifted. Location Contiguous United States of America. Methods Here, we used stable carbon isotope data (i.e. δ 13 C) from 30 years of soil samples, as well as herbivore tissues that date to 1739 CE , to reconstruct coarse‐grain C 3 and C 4 grass composition in North American grassland sites to compare with modern vegetation. We spatially resampled these three datasets to a shared 100‐km grid, allowing comparison of δ 13 C values at a resolution and extent common for climate model outputs and biogeographical studies. Results At this spatial grain, the bison tissue proxy was superior to the soil proxy because the soils reflect integration of local carbon inputs, whereas bison sample vegetation across landscapes. Bison isotope values indicate that historical grassland photosynthetic‐type composition was similar to modern vegetation. Main conclusions Despite major environmental change, comparing modern plot vegetation data to three centuries of bison δ 13 C data revealed that the biogeographical distribution of C 3 and C 4 grasses has not changed significantly since the 1700s. This is particularly surprising given the expected CO 2 fertilization of C 3 grasses. Our findings highlight the critical importance of capturing the full range of physiological, ecological and demographical processes in biosphere models predicting future climates and ecosystems.

Global synthesis of the temperature sensitivity of leaf litter breakdown in streams and rivers - Jennifer J. Follstad Shah; John S. Kominoski; Marcelo Ardón; Walter K. Dodds; Mark O. Gessner; Natalie A. Griffiths; Charles P. Hawkins; Sherri L. Johnson; Antoine Lecerf; Carri J. LeRoy; David W. P. Manning; Amy D. Rosemond; et al. (Global Change Biology, 2017)
Streams and rivers are important conduits of terrestrially derived carbon (C) to atmospheric and marine reservoirs. Leaf litter breakdown rates are expected to increase as water temperatures rise in response to climate change. The magnitude of increase in breakdown rates is uncertain, given differences in litter quality and microbial and detritivore community responses to temperature, factors that can influence the apparent temperature sensitivity of breakdown and the relative proportion of C lost to the atmosphere vs. stored or transported downstream. Here, we synthesized 1025 records of litter breakdown in streams and rivers to quantify its temperature sensitivity, as measured by the activation energy ( E a , in eV ). Temperature sensitivity of litter breakdown varied among twelve plant genera for which E a could be calculated. Higher values of E a were correlated with lower‐quality litter, but these correlations were influenced by a single, N‐fixing genus ( Alnus ). E a values converged when genera were classified into three breakdown rate categories, potentially due to continual water availability in streams and rivers modulating the influence of leaf chemistry on breakdown. Across all data representing 85 plant genera, the E a was 0.34 ± 0.04 eV , or approximately half the value (0.65 eV ) predicted by metabolic theory. Our results indicate that average breakdown rates may increase by 5–21% with a 1–4 °C rise in water temperature, rather than a 10–45% increase expected, according to metabolic theory. Differential warming of tropical and temperate biomes could result in a similar proportional increase in breakdown rates, despite variation in E a values for these regions (0.75 ± 0.13 eV and 0.27 ± 0.05 eV, respectively). The relative proportions of gaseous C loss and organic matter transport downstream should not change with rising temperature given that E a values for breakdown mediated by microbes alone and microbes plus detritivores were similar at the global scale.

Diurnal Fluctuations in Acidification and Hypoxia Reduce Growth and Survival of Larval and Juvenile Bay Scallops (Argopecten irradians) and Hard Clams (Mercenaria mercenaria) - Christopher J. Gobler; Hannah R. Clark; Andrew W. Griffith; Mark W. Lusty (Frontiers in Marine Science, 2017)

Assessing Landscape Change and Processes of Recurrence, Replacement, and Recovery in the Southeastern Coastal Plains, USA - Mark A. Drummond; Michael P. Stier; Roger F. Auch; Janis L. Taylor; Glenn E. Griffith; Jodi L. Riegle; David J. Hester; Christopher E. Soulard; Jamie L. McBeth (Environmental Management, 2015)

Biogeographically distinct controls on C 3 and C 4 grass distributions: merging community and physiological ecology - Daniel M. Griffith; T. Michael Anderson; Colin P. Osborne; Caroline A. E. Strömberg; Elisabeth J. Forrestel; Christopher J. Still (Global Ecology and Biogeography, 2015)
Aim C 4 photosynthesis is an adaptation that maintains efficient carbon assimilation in high‐light, high‐temperature conditions. Due to the importance of C 4 grasses for carbon and surface energy fluxes, numerous models have been proposed to describe their spatial distribution and forecast their responses to climate change. These models often rely on broad climatic predictors (e.g. temperature and precipitation) but fail to integrate other ecologically relevant factors like disturbance and competition, which may modify realized C 3 / C 4 grass distributions. Here, we present a combined evaluation of the contribution of ecological factors and climatic predictors to realized C 3 / C 4 grass distributions. We consider multiple biogeographic regions of N orth A merica using a multisource database of over 40,000 vegetation plots. Location The conterminous U nited S tates of A merica ( USA ). Methods We identified a comprehensive pool of climatic models in the literature and used information theoretic criteria to select a primary climatic predictor of C 3 and C 4 grass distributions. Subsequently, the best model was combined with ecological predictors (e.g. fire, tree cover) using a multiple regression framework and tested within eight regions. Results Surprisingly, grass‐dominated communities across the USA exist largely in C 3 ‐ or C 4 ‐dominated states. Transitions between C 3 / C 4 dominance were best explained by models that integrated temperature and precipitation with ecological factors that varied according to region. For some regions, like E astern T emperate F orests, local ecological factors were comparable in strength to broad‐scale climatic predictors of C 3 / C 4 abundance. Main conclusion Local ecological factors modify C 3 / C 4 grass responses to broad‐scale climatic drivers in ways that manifest at regional scales. In E astern T emperate F orests, for example, C 4 grass abundances are maintained below climatic expectations where tree cover creates light limitation but above expectations where frequent fires reduce tree cover. Thus, local ecological factors, which vary among biogeographic regions, contribute to large‐scale climate disequilibrium.

Effects of two contrasting canopy manipulations on growth and water use of London plane (Platanus x acerifolia) trees - Neil A. Hipps; Michael J. Davies; Joel M. Dunn; Howard Griffiths; Christopher J. Atkinson (Plant and Soil, 2014)

Range expansions across ecoregions: interactions of climate change, physiology and genetic diversity - Marc Rius; Susana Clusella‐Trullas; Christopher D. McQuaid; René A. Navarro; Charles L. Griffiths; Conrad A. Matthee; Sophie von der Heyden; Xavier Turon (Global Ecology and Biogeography, 2014)
Aim Climate change is expected to drive range shifts among a wide array of organisms. Non‐indigenous species ( NIS ) provide a unique opportunity to observe the establishment of range boundaries in a way that cannot be directly seen for native species. Recent studies have indicated that climate change facilitates biological invasions at local scales. However, the generality of these effects is unclear, as there is a dearth of comparative studies that assess how rapid environmental change affects species ranges across taxa and biogeographic provinces. Location The S outh A frican coast and other coastlines across the world. Methods We first studied the distribution of shallow‐marine benthic organisms along the S outh A frican coastline and analysed the global distribution of NIS . We then obtained DNA sequence data from a suite of co‐occurring NIS from along the studied coastline and compared these data with available genetic information from other regions of the world. Subsequently, we conducted physiological experiments to assess how thermal tolerance was related to species distribution. Finally, we analysed ship‐based seawater temperature records and compared these with past changes in the range size and abundance of NIS . These records were used to estimate shipping intensity and NIS propagule pressure. Results We found that NIS with a variety of thermal tolerances and distributions have expanded their ranges and increased in abundance as seawater temperature regimes have changed. We found little interannual variation in shipping transport intensity. Most haplotypes of the studied NIS in S outh A frica were shared with other regions. Main conclusions This study provides empirical evidence that NIS , regardless of their thermal tolerance, range size and genetic variability, are expanding their ranges and increasing in abundance. This trend is uncorrelated with levels of human‐mediated NIS transport but concurrent with changes in seawater temperature, which suggests that climate change fosters the spread and abundance of NIS across multiple spatial scales.

Circumpolar overview and spatial heterogeneity of Antarctic macrobenthic communities - Julian Gutt; Huw J. Griffiths; Christopher D. Jones (Marine Biodiversity, 2013)

MRI volume of the medial frontal cortex predicts financial capacity in patients with mild Alzheimer’s disease - Luke E. Stoeckel; Christopher C. Stewart; H. Randall Griffith; Kristen Triebel; Ozioma C. Okonkwo; Jan A. den Hollander; Roy C. Martin; Katherine Belue; Jacquelynn N. Copeland; Lindy E. Harrell; John C. Brockington; David G. Clark; et al. (Brain Imaging and Behavior, 2013)

Cross-linking of structural proteins in ageing skin: an in situ assay for the detection of amine oxidase activity - Abigail K. Langton; Christopher E. M. Griffiths; Michael J. Sherratt; Rachel E. B. Watson (Biogerontology, 2013)

Genome‐wide analysis of longevity in nutrient‐deprived Saccharomyces cerevisiae reveals importance of recycling in maintaining cell viability - Hazel M. Davey; Emma J. M. Cross; Christopher, L. Davey; Konstantinos Gkargkas; Daniela Delneri; David C. Hoyle; Stephen G. Oliver; Douglas B. Kell; Gareth W. Griffith (Environmental Microbiology, 2012)
Summary Although typically cosseted in the laboratory with constant temperatures and plentiful nutrients, microbes are frequently exposed to much more stressful conditions in their natural environments where survival and competitive fitness depend upon both growth rate when conditions are favourable and on persistence in a viable and recoverable state when they are not. In order to determine the role of genetic heterogeneity in environmental fitness we present a novel approach that combines the power of fluorescence‐activated cell sorting with barcode microarray analysis and apply this to determining the importance of every gene in the Saccharomyces cerevisiae genome in a high‐throughput, genome‐wide fitness screen. We have grown > 6000 heterozygous mutants together and exposed them to a starvation stress before using fluorescence‐activated cell sorting to identify and isolate those individual cells that have not survived the stress applied. Barcode array analysis of the sorted and total populations reveals the importance of cellular recycling mechanisms (autophagy, pexophagy and ribosome breakdown) in maintaining cell viability during starvation and provides compelling evidence for an important role for fatty acid degradation in maintaining viability. In addition, we have developed a semi‐batch fermentor system that is a more realistic model of environmental fitness than either batch or chemostat culture. Barcode array analysis revealed that arginine biosynthesis was important for fitness in semi‐batch culture and modelling of this regime showed that rapid emergence from lag phase led to greatly increased fitness. One hundred and twenty‐five strains with deletions in unclassified proteins were identified as being over‐represented in the sorted fraction, while 27 unclassified proteins caused a haploinsufficient phenotype in semi‐batch culture. These methods thus provide a screen to identifying other genes and pathways that have a role in maintaining cell viability.

Differential expression of elastic fibre components in intrinsically aged skin - Abigail K. Langton; Michael J. Sherratt; Christopher E. M. Griffiths; Rachel E. B. Watson (Biogerontology, 2012)

Sensitization of human bladder tumor cells to TNF-related apoptosis-inducing ligand (TRAIL)-induced apoptosis with a small molecule IAP antagonist - Thomas S. Griffith; Tamara A. Kucaba; Michael A. O’Donnell; Jennifer Burns; Christopher Benetatos; Mark A. McKinlay; Stephen Condon; Srinivas Chunduru (Apoptosis, 2011)

A novel loss-of-function mutation in TP53 in an endometrial cancer cell line and uterine papillary serous carcinoma model - Zhihe Liu; Guanghua Wan; Christopher Heaphy; Marco Bisoffi; Jeffrey K. Griffith; Chien-an A. Hu (Molecular and Cellular Biochemistry, 2007)

Broad-scale analysis of soil microbial community DNA from Upland grasslands - Christopher D. Clegg; Karl Ritz; Bryan S. Griffiths (Antonie van Leeuwenhoek, 1998)